Comparative Chemical Profiling and Biological Potential of Essential Oils of Petal, Choke, and Heart Parts of Cynara scolymus L. Head - Sana Razhan M. Alsubaiei; Hanan A. Alfawaz; Musarat Amina; Nawal M. Al Musayeib; Afaf El-Ansary; Syed Rizwan Ahamad; Omar M. Noman; Jaber A. Maini (Journal of Chemistry)
The essential oil and macroelemental composition of different parts of flower bud (petal, choke, and heart) of Cynara scolymus L. were explored and compared using gas chromatography mass spectrometry (GC-MS) and inductively coupled plasma mass spectrometry (ICP-MS). Overall, 62 organic components were detected in the flower bud based on mass spectra characteristics and retention indices. The essential oil extracted from the petals, choke, and bud showed the presence of thirty-one, twenty-one, and twenty-one compounds, respectively, with linoleic acid and palmitic acid as the major components. 21 components were identified in the oil of the petals, comprising 94.45% of the total oil, in which linoleic acid methyl ester, palmitic acid methyl ester, octadecanoic acid methyl ester, O-α-d-glucopyranoside, and heptyl oct-3-yl ester were the major constituents. Twenty-one compounds, representing 89.13% of the total oil, were detected in the choke oil. Linoleic acid methyl ester, palmitic acid methyl ester, and 2-methyl-1-hexadecanol were the main components. However, the edible heart oil contains twenty compounds, comprising 86.84% of the total oil. Cyclopropane butanoic acid, linoleic acid, methyl ester, and palmitic acid were the major constituents. The analysis executed by ICP-MS revealed the presence of significant amounts of various inorganic elements in all the three samples. The extracted essential oils were tested for antibacterial, antioxidant, and anticancer activities. The results showed that the oil extracted from the petals of C. scolymus flower bud displayed the highest antibacterial, antioxidant, anti-inflammatory, and anticancer effects, as compared to choke and heart oils.